In article <473ptj$pj8 at nntp3.u.washington.edu>,
Joe Felsenstein <joe at evolution.genetics.washington.edu> wrote:
...
>The equation for homozygosity (= 1- heterozygosity) which we call F is
>> F(t+1) = (1-v)^2 [1/(2N) + (1 - 1/(2N)) F(t) ]
>>If we write this as F(t+1) = a + b F(t) where
>> a = 1/(2N)
>> b = (1-v)^2 (1 - 1/(2N))
Oops. I should have said a = (1-v)^2 (1/(2N)) instead.
Fortunately the rest of the formulas in the post are unaffected by that.
-----
Joe Felsenstein joe at genetics.washington.edu (IP No. 128.95.12.41)
Dept. of Genetics, Univ. of Washington, Box 357360, Seattle, WA 98195-7360 USA